Preliminary Trials with Weedicides to Control Shrub Weed Species - Ganguli, B. N. (Indian Forester, 1964)
Preliminary results have shown that common dicot weeds occurring in the forest areas in the arid regions can be effectively controlled by butoxy ethanol ester of 2,4,5- T and 2, 4-D (Bladex-K) as well as mixture of 2, 4-D and 2,4,5-T (Spontox). For complete control as a foliar spray a higher concentration of both these arboricides is necessary. Painting after debarking at the collar region brings about complete eradication of Prosopis juliflora and Zizyphus nummularia and regeneration through root suckers is also completely controlled.